(untitled) (LEARNing Landscapes, 2014)
A researcher in education usually asks questions, selects a random sample, conducts an experiment, and publishes the findings. However, my questions arose from my actual experiences, first as a pupil, and later as a teacher in an elementary school located in a Montreal slum. Examination of the pupils’ permanent record cards indicated that their IQs typically changed between grades three and six. Moreover, the records showed that the efforts of Miss A had not only resulted in the significantly higher IQs of her pupils compared to those of other grade one teachers, but years later, interviews of the same individuals also indicated higher rankings with respect to their subsequent adult status.